End-User Development of Interactive Web-Based Virtual Reality Scenes - Yigitbas, Enes; Klauke, Jonas; Gottschalk, Sebastian; Engels, Gregor (Journal on Computer Languages (COLA))

Towards Enhanced Guiding Mechanisms in VR Training through Process Mining - Yigitbas, Enes; Krois, Sebastian; Gottschalk, Sebastian; Engels, Gregor (Proceedings of the 7th International Conference on Human Computer Interaction Theory and Applications (HUCAPP'23))

Architectural Management of OTF Computing Markets - Gottschalk, Sebastian; Vorbohle, Christian; Kundisch, Dennis; Engels, Gregor; Wünderlich, Nacy V. (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

GaMoVR: Gamification-Based UML Learning Environment in Virtual Reality - Yigitbas, Enes; Schmidt, Maximilian; Bucchiarone, Antonio; Gottschalk, Sebastian; Engels, Gregor (Science of Computer Programming)

Virtual Reality Collaboration Platform for Agile Software Development - Yigitbas, Enes; Witalinski, Iwo; Gottschalk, Sebastian; Engels, Gregor (Proceedings of the 24th International Conference on Product-Focused Software Process Improvement (PROFES 2023))

Situational Business Model Developer: A Tool-support for Situation-speciﬁc Business Model Development - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
The development of business models is a challenging task that can be supported with software tools. Here, existing approaches and tools do not focus on the company’s situation in which the development takes place (e.g., ﬁnancial resources, product type). To tackle this challenge, we used design science research to develop a situation-speciﬁc business model development approach that contains three stages: First, existing knowledge in terms of tasks to do (e.g., analyze competitive advantage), and decisions to be made (e.g., social media marketing) are stored in repositories. Second, the knowledge is used to compose a development method based on the company’s situation. Third, the development method is enacted to develop a business model. This demonstration paper presents a tool-support called Situational Business Model Developer that supports all stages of our approach. We release the tool under open-source and evaluate it with a case study on developing business models for mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Tool Support

Development and Evaluation of a Collaborative Stock Trading Environment in Virtual Reality - Yigitbas, Enes; Gottschalk, Sebastian; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
Due to the proliferation of Virtual Reality (VR) technology, VR is finding new applications in various domains, such as stock trading. Here, traders invest in stocks intending to increase their profit. For this purpose, in conventional stock trading, traders usually make use of 2D applications on desktop or laptop devices. This leads to many drawbacks such as poor visibility due to limited 2D representation, complex interaction due to indirect interaction via mouse and keyboard, or restricted support for collaboration between traders. To overcome these issues, we have developed a novel collaborative, virtual environment for stock trading, which enables stock traders to view financial information and trade stocks with other collaborators. The main results of a usability study indicate that the VR environment, compared to conventional stock trading, shows no significant advantages concerning efficiency and effectiveness, however, we could observe an increased user satisfaction and better collaboration.
Keywords: virtual reality; stock trading; collaboration; usability

Model-driven Continuous Experimentation on Component-based Software Architectures - Gottschalk, Sebastian; Yigitbas, Enes; Engels, Gregor (Proceedings of the 18th International Conference on Software Architecture Companion)
To build successful software products, developers continuously have to discover what features the users really need. This discovery can be achieved with continuous experimentation, testing different software variants with distinct user groups, and deploying the superior variant for all users. However, existing approaches do not focus on explicit modeling of variants and experiments, which offers advantages such as traceability of decisions and combinability of experiments. Therefore, our vision is the provision of model-driven continuous experimentation, which provides the developer with a framework for structuring the experimentation process. For that, we introduce the overall concept, apply it to the experimentation on component-based software architectures and point out future research questions. In particular, we show the applicability by combining feature models for modeling the software variants, users, and experiments (i.e., model-driven) with MAPE-K for the adaptation (i.e., continuous experimentation) and implementing the concept based on the component-based Angular framework.
Keywords: continuous experimentation; model-driven; component-based software architectures; self-adaptation

Detecting Data Incompatibilities in Process-Driven Decision Support Systems - Kirchhoff, Jonas; Gottschalk, Sebastian; Engels, Gregor (Lecture Notes in Business Information Processing)
Decision makers in complex business environments have different goals and constraints and therefore require tailored decision support systems (DSS). Following a low-code approach, a tailored DSS can be created by a decision maker as a process-based composition of existing, interoperable decision support services. Data incompatibilities may be introduced during the design or execution of such a process-driven DSS, e.g., when a service always generates or a decision maker selects data which violates a data constraint of a subsequent service. These incompatibilities cause interrupted or erroneous decision processes. In this paper, we contribute an approach which enables the detection of data incompatibilities in process-driven DSS during process design and execution. Our approach utilizes the JSON Schema specification to define service interfaces and associated type constraints which data produced by services or decision makers can be validated against. We demonstrate our approach in the context of decision support for energy network planning using a prototypical open-source implementation.

Situation-specific Development of Business Models within Software Ecosystems - Gottschalk, Sebastian
The development of new business models is essential for startups to become successful, as well as for established companies to explore new business opportunities. However, developing such business models is a challenging activity. On the one hand, various tasks of business model development methods (BMDMs) need to be performed. On the other hand, different decisions for the business models (BMs) need to be made. Both have to fit the changeable situation of the organization in which the business model is developed to reduce the risk of developing ineffective business models with low market penetration. Therefore, the BMDMs and the BMs must be developed situation-specific. In this thesis, we conduct a design science research study to design a novel approach for the situation-specific development of business models with three stages. In the first stage, we create a method repository with method fragments for the BMDMs and a canvas model repository with modeling fragments for the BMs. Both repositories are filled by the knowledge of domain experts. Out of these repositories, in the second stage, situation-specific BMDMs for developing situation-specific BMs are composed by a method engineer based on the changeable situation of the organization and enacted by a business developer. The business developer collaborates with other stakeholders during the enaction to create artifacts. Moreover, in the third stage, he receives IT support, provided by development support engineers, in different development steps.